Effect of baffles on pressurization and thermal stratification in cryogenic tanks under micro-gravity. (December 2018) - Zuo, Z.Q.; Jiang, W.B.; Huang, Y.H.
Highlights: CFD model for simulating LN2 in a tank with baffle under microgravity is developed. Effect of gravity, fill level, distance, angle and gap on pressure rise is discussed. A 2nd order correlation between liquid fraction and pressure rise is proposed. A structure is proposed to achieve high performance of pressure suppression. Abstract: Researches on the impact of baffles on sloshing suppression of two-phase fluids in storage tanks have been widely conducted in literature, particularly at normal gravity. However, few studies focused on the effect of the baffles on self-pressurization and thermal stratification of the fluids in containers. This paper uses Volume of Fluid (VOF) method to simulate thermal behavior of cryogenics in tanks with different baffle structures in microgravity environment. Groups of gravity levels, fill levels and baffle configurations (distances, angles and gaps) are investigated. Up to 54% reduction in pressurization rate was observed by optimizing the baffle settings, which is an attractive improvement for missions of long term storage of cryogen on orbit.